2003
DOI: 10.1097/01.ta.0000092681.17874.6f
|View full text |Cite
|
Sign up to set email alerts
|

Low-Volume Resuscitation with a Polymerized Bovine Hemoglobin-Based Oxygen-Carrying Solution (HBOC-201) Provides Adequate Tissue Oxygenation for Survival in a Porcine Model of Controlled Hemorrhage

Abstract: Low-volume resuscitation with HBOC-201 provides adequate tissue oxygenation for survival in a porcine model of controlled hemorrhagic shock with no long-term organ dysfunction identified. Although some animals did show mild hepatocellular damage with elevations of aspartate aminotransferase at day 2, these findings did not appear to have clinical relevance, and the enzyme elevations were trending toward normal by the third postoperative day. Decreases in hemoglobin levels at the later time points were expected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 27 publications
2
33
0
2
Order By: Relevance
“…The age of RBCs should be considered in the design of these trials. RBC substitutes, such as bovine hemoglobin, 29 may be an alternative to RBC transfusion in PCI patients.…”
Section: Discussionmentioning
confidence: 99%
“…The age of RBCs should be considered in the design of these trials. RBC substitutes, such as bovine hemoglobin, 29 may be an alternative to RBC transfusion in PCI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of hemoglobin-based oxygen carriers (HBOC) for use as primary resuscitation fluids for hemorrhagic shock (HS) causalities in the pre-hospital setting, where blood is not available (rural trauma or military operations), has recently gained prominence in trauma research [1][2][3][4]. HBOC are chemically modified hemoglobin solutions .…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that HBOC-201 could be an effective low-volume resuscitation fluid in the battlefield, rural areas, or other scenarios where efficient transport of fluid products was of prime importance. The same group of investigators evaluated pigs that had received HBOC transfusion, for evidence of end-organ damage [28]. The parameters used were lab values such as blood-gas analyses, urine output, and jejunal oximetry as well as analyses of different tissues at necropsy performed on post-injury day 3.…”
Section: Properties Of Hboc-201mentioning
confidence: 99%